Symmetries in Quantum Mechanics and Statistical Physics - Junker, Georg (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book collects contributions to the Special Issue entitled "Symmetries in Quantum Mechanics and Statistical Physics" of the journal Symmetry. These contributions focus on recent advancements in the study of PT-invariance of non-Hermitian Hamiltonians, the supersymmetric quantum mechanics of relativistic and non-relativisitc systems, duality transformations for power-law potentials and conformal transformations. New aspects on the spreading of wave packets are also discussed.